The first hundred years : - Goodey, Charles (Boydell Press for Richards, 1976)
Shipbuilding capacity world-wide outstrips demand on an unprecedented scale and the Brish shipbuilding industry is due to be nationalissed during the current parliamentary tern. Richards is just small enough to be left out of this nationalised sector and we see this state of affairs equally as a comfort and also a challenge.